First report for Venezuela of Tibraca limbativentris Stal 1860 (Hemiptera: Pentatomidae), as a vector of the Steneotarsonemus spinki Smiley 1967 (Acari: Tarsonemidae) (Bioagro, 2020)
The rice sheath mite (Steneotarsonemus spinki) is one of the main pests in rice farmer, and can cause losses of up to 90%. One of the methods of dispersion of this arachnid is through the flight of some insects. The forectic relationship between S. spinki and the rice stem bugs (Tibraca limbativentris Stal. and T. obscurata Y.) in different rice farmers of Calabozo (Guárico State) and a sector of Mata Oscura (Anzoátegui County, Cojedes State) was studied. It was found for the first time in Venezuela that individuals of T. limbativentris represent an important mechanism of transport and dispersal of the rice sheath mite. No forectic relationship was found between S. spinki and T. obscurata. This registry is basic to be used as information to develop key strategies in the integrated management of the populations of both pest species in the rice farms in Guárico and Cojedes States.
Keywords: Cojedes; Guárico; rice sheath mite